If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24y = -24x + -96 Reorder the terms: 24y = -96 + -24x Solving 24y = -96 + -24x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '24'. y = -4 + -1x Simplifying y = -4 + -1x
| 77x^2+x-6= | | x^2-64x+16=0 | | 3t+1=t+7 | | 17x+26=111 | | 9x(-3+5)=3x(-3-3)+6x-3 | | 9(-3+5)=3(-3-3)+6x-3 | | 3/2y=2/3y+5 | | 9(-3+5)=3(-3-3+6x-3) | | 3x-1/5=-8 | | -3=-3+a | | -5-1x=8 | | 8x+18=62 | | 4u-33=7(u-6) | | 3(-x^2+2x-10)=0 | | x^2-11x-6=-9x+2 | | 17(200)+22x=4148 | | 9+4p-2p=-3-4p | | 4x^2-9x+15=6x+1 | | 5(20x+75)=1475 | | 4sin(6x)=2 | | 5/h=10/30 | | 6x-3=-5 | | 21-x=-1 | | X^2-6x+14=o | | 13x-7=4x-1 | | 2/15=c/72 | | 21-3y=24 | | y=lx-1l | | 102-4(7*3)= | | (2t+1)(t+1)-2(t+1)=0 | | 3/5(5x-4)=18 | | 8c+4=4(2c-3) |